Making Institutional Repositories Work - Wesolek, Andrew, 1983-; Scherer, David, 1984-; Callicott, Burton B., 1968- (Book collections on Project MUSE., 2016)
Making International Repositories Work, arranged in five thematic sections, is intendede to take the pulse of institutional repositories - to see how they have matured and what can be expected from them, as well as introduce what may be the future role of the institutional repository. This collection of essays takes novices as well as seasoned practitioners through the practical and conceptual steps necessary to develop a functioning institutional repository, customized to the needs and culture of the home institution. -- from back cover.